(untitled) (Entrepreneurship Journal for Finance and Business, 2024)
Research aimed to present German cost accounting(GPK) as a methodology for estimating flexible costs, and a more comprehensive system than most traditional cost systems in estimating costs, adopts a variable cost approach that is characterized by being proportional costs that reflect the direct proportional relationship between variable costs and productive units, as the conceptual structure of German cost accounting (GPK) consists of four elements represented in cost element accounting, cost center accounting, production unit accounting and multi-level contribution margin accounting, which is a more accurate and detailed approach than The single-level contribution margin used in traditional cost accounting, and the research sample was the Institute of Management / Rusafa one of the formations of the Middle Technical University(MTU), and the research reached a set of conclusions, the most important of which was; that German cost accounting (GPK) accounting is more sophisticated and comprehensive than traditional cost systems as it unites and addresses all the needs of administrative, accounting and cost functions and adopts high operating modeling in planning, organization and control, and thus provides more accurate data that helps in making clearer decisions, and that the contribution margin is multiple. Levels are an appropriate analytical tool to rationalize a variety of non-routine decisions, as they provide a more detailed view of product costs in a way that helps companies identify the products that achieve the most profitability, and in light of these conclusions, the research proposed a set of recommendations, the most important of which was; The need to adopt German cost accounting as it is a method of planning and control that provides tools for planning and controlling costs by allocating resources to the most profitable activities more effectively and efficiently, The need to adopt contribution margin analysis Multi-level when making production and pricing decisions because of its role in identifying the most profitable products to develop and unprofitable to stop, and this analysis also helps determine the best mix of products and provides companies with a more accurate view of the profitability of each product.